Office is loading: storytelling of homeworking - Barone, Tiziana (E|C, 2021)
Watchword of 2020: Smartworking, but it’s better to say homeworking. With lockdown imposed by the spread of the Covid-19 virus, most companies used several digital solutions in extremely short times compared to those that normally involve cultural changes. Staying at home has become a requirement in relation to an external, urban life that has become “forbidden”. Moreover, the private spaces of home had to host the public side of work, giving rise to a series of semantic oppositions and registering a strong interdiscursion both of the work space (using different languages), both in business practices. In this paper, I develop an analysis on a corpus of (smartworking) homeworking spaces about a group of participants in a laboratory carried out in Sapienza in November 2020.